2007
DOI: 10.3758/bf03193294
|View full text |Cite
|
Sign up to set email alerts
|

Bias in memory predicts bias in estimation of future task duration

Abstract: It often takes people longer than planned to finish tasks. Even though people are aware that their estimates have come up short in the past, they continue to underestimate the duration of future projects. Studies have shown underestimation for such tasks as writing papers, performing everyday and school tasks, completing a computer assignment (Buehler, Griffin, & Ross, 1994;Connolly & Dean, 1997;Griffin & Buehler, 1999;Koole & Spijker, 2000;Newby-Clark, Ross, Buehler, Koehler, & Griffin, 2000;Taylor, Pham, Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 46 publications
2
61
0
3
Order By: Relevance
“…Short tasks are remembered as taking longer than they actually did, which in turn will cause overestimations of how long a short task will require in the future. Consistent with this idea, researchers have found that there is a similar effect of experience with a task on both remembered and predicted duration (Roy & Christenfeld, 2007) and that previous experience affects prediction for how long a task will take (Thomas, Handley, & Newstead, 2007). Further, it is not even clear how people could make a prediction of duration that is even moderately accurate without some reference to memories of how long similar tasks have taken in the past.…”
Section: The Relationship Between Memory and Predictionmentioning
confidence: 66%
See 2 more Smart Citations
“…Short tasks are remembered as taking longer than they actually did, which in turn will cause overestimations of how long a short task will require in the future. Consistent with this idea, researchers have found that there is a similar effect of experience with a task on both remembered and predicted duration (Roy & Christenfeld, 2007) and that previous experience affects prediction for how long a task will take (Thomas, Handley, & Newstead, 2007). Further, it is not even clear how people could make a prediction of duration that is even moderately accurate without some reference to memories of how long similar tasks have taken in the past.…”
Section: The Relationship Between Memory and Predictionmentioning
confidence: 66%
“…An index was created by taking the log of the ratio of estimated duration to actual duration in order to assess accuracy of estimates (Roy & Christenfeld, 2007). This index, which we refer to as log proportional error, has a number of benefits.…”
Section: Dependent Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Another account of the planning fallacy holds that underestimation occurs not because information about previous tasks is neglected but because it is inaccurately remembered (Roy, Christenfeld, & McKenzie, 2005). Whilst there is support for each account (e.g., Buehler et al, 1994;Roy & Christenfeld, 2007;Thomas & Handley, 2008), the research emphasis has been on calibration (Do predictions accord with actual and recollected duration?) and content (Do people focus on the unique features of the target task?…”
mentioning
confidence: 99%
“…However, bias in remembered duration often appears to be due to task characteristics such as novelty (Boltz et al, 1998;Hinds, 1999;Roy and Christenfeld, 2007;Tobin et al, 2010), relative duration (Yarmey, 2000;Tobin and Grondin, 2009), size of potential estimation anchors (Thomas and Handley, 2008), and duration since completion . These tasks characteristics may alter attention that is paid to the task (Thomas and Weaver, 1975) or memory storage size associated with the task (Ornstein, 1969;Block and Reed, 1978) and bias estimation.…”
Section: Optimism In Time Estimation?mentioning
confidence: 99%